Anatomical features of the cervical spinal canal in Chiari I deformity with presyrinx: A case-control study. Issue 5 (October 2017) - Gadde, Judith A; Shah, Vinil; Liebo, Greta B; Ringstad, Geir A; Pomeraniec, I Jonathan; Bakke, Soren J; Fric, Radek; Ksendzovsky, Alexander; Jane, John A; Schwartz, Erin S; Haughton, Victor
Purpose: The relationship between syringomyelia and presyrinx, characterized by edema in the spinal cord, has not been firmly established. Patients with syringomyelia have abnormal spinal canal tapering that alters cerebrospinal fluid flow dynamics, but taper ratios in presyrinx have never been reported. We tested the hypothesis that presyrinx patients have abnormal spinal canal tapering. Materials and methods: At six medical institutions, investigators searched the PACS system for patients with Chiari I and spinal cord edema unassociated with tumor, trauma, or other evident cause. In each case taper ratios were calculated for C1 to C4 and C4 to C7. In two age- and gender-matched control groups, Chiari I patients with no syringomyelia and patients with normal MR scans, the same measurements were made. Differences between groups were tested for statistical significance with t tests. Results: The study enrolled 21 presyrinx patients and equal numbers of matched Chiari I and normal controls. C4 to C7 taper ratios were positive and steeper in presyrinx patients than in the normal controls ( p = 0.04). The upper cervical spine, C1 to C4, tapered negatively in cases and controls without significant differences between the groups. The difference in degree of tonsillar herniation was statistically significant between presyrinx patients and Chiari I controls ( p = 0.01). Conclusions: Presyrinx patients have greater than normal positive tapering in the lower cervical spine and greater degree of tonsillar herniation than the controls.